PENILAIAN KERENTANAN SEKTOR KONSTRUKSI PASCA BENCANA BANJIR SEBAGAI DASAR STRATEGI PENGURANGAN RISIKO BENCANA GEMPA BUMI DI KOTA LANGSA, ACEH - Ari Juanda; rajib muammar; arissa sabilla; haikal fajri (Program Studi Teknik Sipil, Fakultas Teknik. Universitas Samudra, 2026)
Langsa City, Aceh, is an area prone to both flooding and earthquakes. Recurrent flooding can deteriorate building conditions, including foundation damage, wall cracking, material degradation, and reduced structural performance, which may increase vulnerability to future earthquake events. This study aims to assess the vulnerability of the construction sector following flood disasters as a basis for developing earthquake risk reduction strategies in Langsa City. A descriptive qualitative approach was employed using field observations and in-depth interviews. The collected data were analyzed through thematic analysis based on three dimensions: technical, socio-cultural, and political-economic aspects. The findings reveal that construction sector vulnerability in Langsa City is multidimensional. From the technical aspect, vulnerability is associated with material deterioration, wall cracks, and inadequate drainage systems. From the socio-cultural aspect, limited public awareness of earthquake-resistant construction practices and reliance on traditional building experience contribute to increased vulnerability. From the political-economic aspect, financial constraints, unequal distribution of rehabilitation assistance, and weak construction oversight further exacerbate risks. The study concludes that reducing earthquake vulnerability in post-flood areas requires integrated efforts, including structural strengthening, drainage improvement, community education on disaster-resilient construction, and the incorporation of flood and earthquake risk considerations into local development policies.